Training and Development of Competencies as a Mechanism to Improve the Competitiveness of Organisations - TheCase of Sidal Group - merzouki, Yasser (Milev Journal of Research and Studies, 2021)
Competencies can contribute to building a structured model that can be used to integrate management practices throughout the organisation. By enhancing the harmonization of recruitment practices, performance management, training, development and rewards to improve the organisation's competitiveness. To achieve this, the study used a questionnaire consisting of 28 items to collect preliminary data from the sample of 239 researchers. The research hypotheses were formulated based on the collected data and tested using SPSS. This resulted in several conclusions. Most importantly, training plays a significant role in improving competency performance, which in turn contributes to enhancing the competitive advantage of the organisation. Hence, the paper concludes that there is a strong correlation between the development of competencies and competitive advantage.